PPARγ activation but not PPARγ haplodeficiency affects proangiogenic potential of endothelial cells and bone marrow-derived progenitors - Kotlinowski, Jerzy (Cardiovasc Diabetol, 2014)
BACKGROUND: Peroxisome proliferator-activated receptor-γ (PPARγ) agonists, which have been used as insulin sensitizers in diabetic patients, may improve functions of endothelial cells (ECs). We investigated the effect of PPARγ on angiogenic activities of murine ECs and bone marrow-derived proangiogenic cells (PACs). METHODS: PACs were isolated from bone marrow of 10–12 weeks old, wild type, db/db and PPARγ heterozygous animals. Cells were cultured on fibronectin and gelatin coated dishes in EGM-2MV medium. For in vitro stimulations, rosiglitazone (10 μmol/L) or GW9662 (10 μmol/L) were added to 80% confluent cell cultures for 24 hours. Angiogenic potential of PACs and ECs was tested in vitro and in vivo in wound healing assay and hind limb ischemia model. RESULTS: ECs and PACs isolated from diabetic db/db mice displayed a reduced angiogenic potential in ex vivo and in vitro assays, the effect partially rescued by incubation of cells with rosiglitazone (PPARγ activator). Correction of diabetes by administration of rosiglitazone in vivo did not improve angiogenic potential of isolated PACs or ECs. In a hind limb ischemia model we demonstrated that local injection of conditioned media harvested from wild type PACs improved the blood flow restoration in db/db mice, confirming the importance of paracrine action of the bone marrow-derived cells. Transcriptome analysis showed an upregulation of prooxidative and proinflammatory pathways, and downregulation of several proangiogenic genes in db/db PACs. Interestingly, db/db PACs had also a decreased level of PPARγ and changed expression of PPARγ-regulated genes. Using normoglycemic PPARγ(+/−) mice we demonstrated that reduced expression of PPARγ does not influence neovascularization either in wound healing or in hind limb ischemia models. CONCLUSIONS: In summary, activation of PPARγ by rosiglitazone improves angiogenic potential of diabetic ECs and PACs, but decreased expression of PPARγ in diabetes does not impair angiogenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12933-014-0150-7) contains supplementary material, which is available to authorized users.